Tissue engineered bone models of prostate cancer metastasis - Tay, Zong Qing (2019)
Prostate cancer (PCa) metastasis has been one of the most fatal cause of cancer-related condition. It has been identified that the disseminated tumour cells (DTCs) of prostate cancer tumour has a tendency to home to and engraft on bone marrow niche, a phenomenon which was found similar to other forms of cancer such as breast, melanoma,and lung cancer. Despite traditional in vivomodels are able to offer a complex environment and significant physiological interactions, their benefits are limited by the difficulty of cell imaging and differences in species. Emerging in vitro techniques address this issue by employing tissue-engineered construct that are capable of provide clearer information on the metastatic mechanism, albeit on a simplified scale. In this study, a PCa metastatic model was constructed in a microfluidic device for future studies on evaluating and characterising the migration of PCa cells. A pre-metastatic bone mar-row niche comprises stromal cells and bone matrix are replicated in the model with osteogenic differentiated mesenchymal stem cells (MSCs) and type I collagen (Col1) respectively. A bone metastatic PCa cell line is used to represent DTC pre-colonisation. A simple image processing tool was also developed which may aid the relevant research in investigating the proliferation, differentiation and morphology of spheroids.